Video Eksplorasi Keanekaragaman Flora Gunung Pundak Sebagai Media Pembelajaran Untuk Peserta Didik Kelas X - Wulandari, Anggun; Ami, Mucharommah Sartika; Nisa’, Izzatin (Universitas KH. A. Wahab Hasbullah, 2025)
Biodiversity material is one of the materials that requires many examples of real objects related to nature. Based on the results of interviews with biology subject teachers at Madrasah Aliyah Mambaul Ulum Megaluh, it is known that students are very enthusiastic when the teacher displays video media as an introduction to learning. However, instructional videos containing material on biodiversity (especially flora) are still not available. Therefore, researchers develop exploration video learning media. The objectives of this study were to: (1) describe the feasibility of exploratory videos of Mount Pundak flora diversity based on the validation of material experts and instructional media experts, (2) describe the attractiveness of the exploration video of Mount Pundak flora diversity based on the responses of students. This research is a development research using the ADDIE model, consisting of 5 stages: Analysis-Design-Develop-Implement-Evaluate. Feasibility is measured using the validity test by material expert validators and media expert validators. In addition, related to the attractiveness of exploration videos, a response test was carried out on 10 students at Madrasah Aliyah Mambaul Ulum Megaluh who had studied biodiversity material by filling out a questionnaire via google form. The results showed that the media for exploring the diversity of flora on Mount Pundak based on the evaluation of the material expert validator obtained a value of 81.67% which means very feasible, the learning media expert validator obtained a score of 88% which means very feasible, and the response of students obtained a value of 89.8. % which means very interesting. This exploration video media needs to be improved based on criticism and suggestions from material expert validators and media experts. The video media for exploring the diversity of the flora of Mount Pundak can be used for classroom learning provided that further development research is carried out and more extensive testing, so that it is obtained that the exploration video media has been tested for validity and is ready to use